Highly water-reducing powder preparation for dry mortar
Patent Information
- Application Number
- JP2021547484
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-03-26
- Filing Date
- 2020-03-26
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-03-26
Smart Images

Figure 0007630434000028 
Figure 0007630434000001 
Figure 0007630434000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a PCE-type copolymer in powder form which is redispersible in water, to the preparation of this PCE-type copolymer in powder form, and to the use of such a powdered PCE-type copolymer for modifying dry mortar. [Background technology]
[0002] For many years, copolymers of polycarboxylates and polyalkylene glycols (PCEs) have been known as dispersing aids for aqueous dispersions, particularly those of mineral binders. PCEs act as superplasticizers and reduce the amount of water required to obtain a certain level of fluidity in a given unset mineral binder composition. Reduction of water in mineral binder compositions, particularly cementitious compositions, is desirable to reduce separation of solid components in the unset composition and increase the compressive strength of the set composition.
[0003] Nowadays, dry mortars pre-batched at factories are used in new construction and renovation works. Such dry mortars have the advantage of improved consistency of properties such as flowability, hardening kinetics and ultimate strength over mortars batched at the job site. The use of PCE in dry mortars requires the PCE to be in a stiff, preferably powder form. Furthermore, stiff PCE reduces the costs associated with transporting and storing the PCE, especially since dry PCE is redispersible in water and therefore can be easily formed into aqueous solutions or dispersions at the site of use.
[0004] WO 2006 / 133933 discloses PCE type copolymers of olefinically unsaturated monocarboxylic acid monomers copolymerized with unsaturated long chain polyalkylene glycol ether monomers. The copolymers can be spray dried to form powders. However, the disclosed copolymer configuration is not optimized for the spray drying process. This results in caking powders and particle size distributions that are not optimal for use in dry mortars.
[0005] WO 2006 / 129883 discloses PCE type copolymers with a degree of neutralization less than 50% resulting in improved micronization properties. Micronization can be by various means including spray drying process. One drawback is that due to the low degree of neutralization, there still remains a high tendency for powder caking.
[0006] WO 00 / 47533 discloses powdered PCE-based polymeric compositions containing mineral supports, including silica. These powders are reported to have improved powder flow and improved anti-caking properties when compared with powders of the same PCE-type copolymers derived from a spray drying process. One drawback of these powders is that they cannot be easily redispersed to re-prepare a stable aqueous polymer dispersion.
[0007] CN Patent No. 101824125 discloses PCE type copolymers with polyalkylene glycol chains with molecular weights of 600-2,000 g / mol. A spray drying method to obtain powder products is also disclosed. However, the disclosed spray drying process operates at high temperatures, which requires higher energy input and may cause decomposition of the PCE type copolymer during spray drying.
[0008] China Patent No. 101962273 discloses a process for preparing powdered PCE type copolymers with inorganic particles in a spray drying process. However, in order to obtain acceptable powder quality, a significant amount of mineral carrier needs to be added in the spray drying process. In addition, the disclosed spray drying process is operated at high temperature, which requires higher energy input and may cause the PCE type copolymer to be decomposed during spray drying.
[0009] Finally, US Patent No. 7,030,178 discloses powder dispersants for hydraulic compositions based on PCE type copolymers with a degree of alkoxylation in the side chains of 45-150, a ratio of monomers with alkoxylated side chains of 15-45 mol % and a degree of neutralization of carboxylic acid groups of 70-80%. Spray drying is described as a method for obtaining said powder dispersants. One drawback is that with the disclosed degree of neutralization there is still a significant tendency towards powder caking. Summary of the Invention [Problem to be solved by the invention]
[0010] Therefore, there is a need for a powdered PCE composition that is easily preparable by spray drying and that overcomes the above-mentioned drawbacks.
[0011] The present invention aims to provide a powdered PCE-type copolymer obtainable by spray drying, in particular whose fineness and anticaking properties, as well as its effect on the water reducing capacity and slump life in mineral binder compositions, should be improved over the current state of the art.
[0012] It is another object of the present invention to provide a spray drying process for producing this powdered PCE-type copolymer.
[0013] It is yet another object of the present invention to provide a method and use of said powdered PCE type copolymer for improving mineral binder compositions, especially dry mortars. [Means for solving the problem]
[0014] Surprisingly, it has been found that the object of the invention can be achieved according to claim 1 by a powder copolymer P which comprises at least 80% by weight, preferably at least 85% by weight, more preferably at least 90% by weight, each based on the total weight of the powder, of PCE type copolymers which comprise: (a) a molar portion of the structural unit S1 of formula I [ka] (b) b moles of structural unit S2 of formula II [ka] (c) c moles of structural unit S3 of formula III [ka] (d) d molar parts of structural unit S4 of formula IV [ka] During the ceremony, Each M is independently H + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; Each R u each independently represents a hydrogen atom or a methyl group; Each R v represent, independently of one another, hydrogen or COOM, m=0, 1, 2 or 3; p=0 or 1, Each R 1 and each R 2 are mutually independent, C1 to C 20 -Alkyl, C1-C20 -Cycloalkyl, C1-C 20 -alkylaryl, or -[AO] n -R 4 represents Where A=C2-C4-alkylene and R 4 H, C1~C 20 -Alkyl, C1-C 20 -Cyclohexyl or C1-C 20 -alkylaryl, and n = 2 to 350, Each R 3 is, independently of the others, NH2, -NR 5 R 6 , -OR 7 NR 8 R 9 represents Here, R 5 and R 6 are mutually independent, C1~C 20 -Alkyl, C1-C 20 -cycloalkyl, C1~C 20 -Alkylaryl or C1-C 20 -aryl, or a hydroxyalkyl- or acetoxyethyl- (CH3-CO-O-CH2-CH2-), or a hydroxyisopropyl- (HO-CH(CH3)-CH2-), or an acetoxyisopropyl group (CH3-CO-O-CH(CH3)-CH2-); Or R 5 and R 6 together form a ring of which the nitrogen is a part to form a morpholine or imidazoline ring, R 7 is a C2-C4 alkylene group, Each R 8 and R 9 are mutually independent, C1~C 20 -Alkyl, C1-C 20 -Cycloalkyl, C1-C 20 -Alkylaryl, C1-C 20 -aryl or hydroxyalkyl group, and a, b, c and d represent the molar parts of the structural units S1, S2, S3 and S4; Where: a / b / c / d / =(0.1~0.9) / (0.05~0.9) / (0.0~0.8) / (0.0~0.8), where a+b+c+d=1, and This powder copolymer P is a D90 value of <250 μm, preferably <225 μm, in particular <210 μm; A D10 value of <60 μm, preferably <50 μm, in particular <40 μm, and A D50 value of 70 to 130 μm, preferably 75 to 120 μm, in particular 80 to 100 μm The particle size distribution is It is characterized by:
[0015] It has been found that the above powder copolymers P can be advantageously used in dry mortar formulations to reduce the water demand in the dry mortar and / or to increase the fluidity of the composition according to said dry mortar.
[0016] Another advantage of the powdered copolymer P of the invention is that mineral binder compositions containing this powdered copolymer P are less prone to separation after mixing with mixing water.
[0017] Yet another advantage of the present invention is that the powdered copolymer P results in an improved slump life of the mineral binder composition after mixing with water, when compared to an identical mineral binder composition that does not contain said powdered copolymer P but does contain a state-of-the-art PCE type copolymer.Improved slump life means that there is a minimal change in slump flow after a certain time after mixing the mineral binder composition with water.
[0018] Finally, an advantage of the powdered copolymer P of the invention is the higher compressive strength of the mineral binder composition after hardening of this powdered copolymer P, especially when measured 1 or 3 days after mixing with water, when compared with mineral binder compositions having the same level of flowability but containing PCE type copolymers of the current state of the art.
[0019] Further aspects of the invention are the subject matter of further independent claims. Particularly preferred embodiments of the invention are the subject matter of the dependent claims.
[0020] In the context of the present invention, the expression "mineral binder" refers in particular to a binder that reacts in a hydration reaction in the presence of water to form a solid hydrate or hydrate phase. It can be, for example, a hydraulic binder (e.g. cement or hydraulic lime), a latent hydraulic binder (e.g. slag), a pozzolanic binder (e.g. fly ash) or a non-hydraulic binder (gypsum plaster or white stucco). A "mineral binder composition" is therefore a composition comprising at least one mineral binder.
[0021] According to an embodiment, the mineral binder or mineral binder composition contains a hydraulic binder, preferably cement. Particularly preferred is a cement with a cement clinker content of 35% by weight or more. In particular, the cement is of CEM I, II, III (according to standard EN 197-1), or a calcium aluminate cement (according to standard EN 14647:2006-01), or a calcium sulfoaluminate cement, or a mixture thereof. The proportion of hydraulic binder in the total amount of mineral binder is advantageously at least 5% by weight, in particular at least 20% by weight, preferably at least 35% by weight, in particular at least 65% by weight. In a further advantageous embodiment, the mineral binder is to a certain extent composed of at least 95% by weight of hydraulic binder, in particular cement clinker.
[0022] In an advantageous embodiment, the cement further contains at most 40% by weight, preferably at most 35% by weight, in particular at most 20% by weight, of calcium sulfate, each based on the total dry weight of the cement, which may be present in the form of calcium sulfate hemihydrate, calcium sulfate dihydrate and / or anhydrate.
[0023] According to a further embodiment, the binder composition comprises other binders in addition to or instead of the hydraulic binder. These are in particular latent hydraulic and / or pozzolanic binders. Suitable latent hydraulic and / or pozzolanic binders are, for example, slag, fly ash and / or silica dust. In an advantageous embodiment, the mineral binder contains 5 to 95% by weight, in particular 5 to 65% by weight, in particular 15 to 35% by weight of latent hydraulic and / or pozzolanic binder.
[0024] As used in the context of the present invention, the term "aggregate" refers to a mineral material that is non-reactive in the hydration reaction of the mineral binder. The aggregate can be any aggregate typically used in cementitious substances such as concrete, mortar, screed, rendering, grout, coating, putty, etc. Typical aggregates are, for example, rock, crushed stone, gravel, slag, limestone, sand, recycled concrete, perlite or vermiculite.
[0025] In the context of the present invention, "dry mortar" refers to a composition containing at least one mineral binder as described above, typically aggregates, and additives selected from the group of plasticizers, superplasticizers, rheology modifiers, set retarders, air entrainers, deaeration agents, corrosion inhibitors, fibers, synthetic organic polymers, expansion agents, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducers and / or antimicrobial agents. Dry mortars may contain small amounts of water. Dry mortars have a solid consistency, in particular a powder consistency. Dry mortars are typically pre-batched in a factory and delivered to the job site. Dry mortars can be formulated to be used as repair mortars for concrete, as screeds, renderings, coatings, putties, grouts or hydraulic cements, as well as for water- or fire-resistant applications.
[0026] In the context of the present invention, a "particle size distribution" is a list of values that defines the relative amount of particles present based on their diameter. Particle size distributions can be described by different D values. For example, the D10 value is the diameter of the particles below which 10% of the particles of a given distribution are smaller and above which 90% of the particles of a given distribution are larger. And the D90 value is the diameter below which 90% of a given sample contains particles with a diameter smaller than this value. Unless otherwise specified, the term "particle size" refers for the present purposes to the median value of the particle size distribution of a solid. This median value is taken as the D50 value of a given particle size distribution and consists of the value of the particle size at 50% of the cumulative distribution. The D50 value is usually interpreted as the particle size above which 50% of the particles of a given distribution are larger and below which 50% of the particles of a given distribution are smaller. Therefore, D50 is a numerical median.
[0027] The particle size distribution defined above, and therefore the different D values as well as the particle size, can in particular be measured by laser light scattering, preferably in accordance with the standard ISO 13320: 2009. In particular, a Mastersizer 2000 instrument can be used for this purpose together with a Hydro 2000G dispersion unit and the Mastersizer 2000 software (manufactured by Malvern Instruments GmbH, Germany).
[0028] In the context of the present invention, the term "slump life" refers to the time after mixing the mineral binder composition with water until the slump starts to decrease, as measured, for example, by ASTM C143. Generally, a longer slump life is advantageous since the mineral binder composition will be workable for a longer time.
[0029] The powder copolymer P of the invention is a powder copolymer P which comprises at least 80% by weight, preferably at least 85% by weight, more preferably at least 90% by weight, each based on the total weight of the powder, of PCE type copolymers comprising: (a) a molar portion of the structural unit S1 of formula I [ka] (b) b moles of structural unit S2 of formula II [ka] (c) c moles of structural unit S3 of formula III [ka] (d) d molar parts of structural unit S4 of formula IV [ka] During the ceremony, Each M is independently H + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; Each Ru each independently represents a hydrogen atom or a methyl group; Each R v represent, independently of one another, hydrogen or COOM, m=0, 1, 2 or 3; p=0 or 1, Each R 1 and each R 2 are mutually independent, C1 to C 20 -Alkyl, C1-C 20 -Cycloalkyl, C1-C 20 -alkylaryl, or -[AO] n -R 4 represents Where A=C2-C4-alkylene and R 4 H, C1~C 20 -Alkyl, C1-C 20 -Cyclohexyl or C1-C 20 -alkylaryl, and n = 2 to 350, Each R 3 is, independently of the others, NH2, -NR 5 R 6 , -OR 7 NR 8 R 9 represents Here, R 5 and R 6 are mutually independent, C1~C 20 -Alkyl, C1-C 20 -cycloalkyl, C1~C 20 -Alkylaryl or C1-C 20 -aryl, or a hydroxyalkyl- or acetoxyethyl- (CH3-CO-O-CH2-CH2-), or a hydroxyisopropyl- (HO-CH(CH3)-CH2-), or an acetoxyisopropyl group (CH3-CO-O-CH(CH3)-CH2-); Or R 5 and R 6 together form a ring of which the nitrogen is a part to form a morpholine or imidazoline ring, R 7 is a C2-C4 alkylene group, Each R 8 and R 9 are mutually independent, C1~C 20 -Alkyl, C1-C 20 -Cycloalkyl, C1-C 20 -Alkylaryl, C1-C 20 -aryl or hydroxyalkyl group, and a, b, c and d represent the molar parts of the structural units S1, S2, S3 and S4; Where: a / b / c / d=(0.1~0.9) / (0.05~0.9) / (0~0.8) / (0.0~0.8), In particular, a / b / c / d=(0.3~0.9) / (0.05~0.7) / (0~0.3) / (0.0~0.4), However, a+b+c+d=1.
[0030] PCE type copolymers having n=8-250, more preferably n=11-200, even more preferably n=20-150, most preferably n=30-125, especially n=50-115 have been particularly advantageous for use in dry mortars.
[0031] Advantageously, the molar portions of the structural units S1, S2, S3 and S4 are selected as follows: a / b / c / d=(0.3-0.9) / (0.05-0.9) / (0-0.3) / (0-0.4), preferably a / b / c / d=(0.3-0.9) / (0.05-0.7) / 0 / 0.
[0032] According to a particularly advantageous embodiment, the ratio a / b is between 0.5 / 1 and 15 / 1, preferably between 1 / 1 and 11 / 1, more preferably between 1.5 / 1 and 9 / 1, most preferably between 3 / 1 and 8 / 1, in particular between 6 / 1 and 7 / 1. A ratio a / b within the preferred limits results in improved performance of the powder copolymer P when used in mineral binder compositions, in particular in dry mortars. Powder copolymers P having an a / b ratio within the preferred limits therefore result in a higher initial fluidity and a higher compressive strength of the mineral binder or mineral binder composition when compared to powder copolymers P having other a / b ratios.
[0033] According to a particularly advantageous embodiment, R u and R v each represents hydrogen or a methyl group, m=1, p=0, and R 1 HA-[AO] n -R 4 where A represents C2-alkylene, n=50-115, and R 4 is selected from H or CH3.
[0034] Preferably, the average molecular weight (Mw) of the PCE type copolymer is between 5,000 and 150,000 g / mol, in particular between 10,000 and 100,000 g / mol. The average molecular weight is in particular measured by gel permeation chromatography (GPC) using polyethylene glycol (PEG) as standard.
[0035] In particular, the structural units S1, S2, S3 and S4 together have a composite molecular weight which amounts to at least 50 wt.-%, preferably at least 90 wt.-%, in particular at least 95 wt.-%, each based on the total dry weight of the PCE type copolymer.
[0036] Methods for producing such PCE type copolymers are known in the art. Two main methods are used industrially in the synthesis of such PCE type copolymers. The first method is the radical polymerization of ethylenically unsaturated monomers. The side chains of the resulting PCE type copolymers are already attached to the monomer units. PCE type copolymers with the desired structure and properties are obtained by a specific selection and ratio of monomers in the polymerization reaction solution, in particular the amount of acrylic and methacrylic acid monomers. Such radical polymerizations and the resulting PCE type copolymers are described, for example, in WO 2012 / 084954.
[0037] In a preferred embodiment of the present invention, the PCE type copolymer is obtained by radical polymerization. Typically, the radical polymerization is preferably regulated with sodium hypophosphite as a regulator. In a particularly preferred embodiment, the radical polymerization is carried out at room temperature.
[0038] In the second method, known as homopolymerization reactions, a polycarboxylic acid backbone is synthesized in a first step. Side chains are then attached to this polycarboxylic acid backbone by, for example, esterification, amidation or etherification reactions involving alcohols, amines, etc. Such homopolymerization reactions as well as the resulting PCE-type copolymers are described, for example, in EP 1 138 697 and WO 2005 / 090416.
[0039] Additional monomers can be contained in the PCE type copolymer of the present invention.Examples of such additional monomers are styrene, α-methylstyrene, vinyl acetate, isobutylene, diisobutylene, cyclopentadiene, ethylene, propylene, N-vinylpyrrolidone, acrylamide, methacrylamide, methyl vinyl ether, ethyl vinyl ether, allylsulfonic acid, acrylamidomethylpropenesulfonic acid, styrenesulfonic acid, butadiene and acrylonitrile.The sum of the molecular weight of any additional monomers contained in the PCE type copolymer of the present invention is less than 50% by weight, preferably less than 10% by weight, particularly less than 5% by weight, based on the total dry weight of the PCE type copolymer, respectively.
[0040] The powdery copolymer P according to the invention is characterized by a particle size distribution with a D90 value of <250 μm, preferably <225 μm, in particular <210 μm, a D10 value of <60 μm, preferably <50 μm, in particular <40 μm, and a D50 value of 70 to 130 μm, preferably 75 to 120 μm, in particular 80 to 100 μm.
[0041] The powdered copolymers P of the invention are obtainable by spray drying aqueous solutions of the PCE type copolymers described above.
[0042] The concentration of the PCE type copolymer in the aqueous solution before spray drying is not particularly limited. However, it may be preferable to use an aqueous solution having a concentration of PCE type copolymer of at least 20% by weight, more preferably at least 40% by weight, and not more than 75% by weight, each based on the total weight of the aqueous solution.
[0043] The pH of the aqueous solution of the PCE type copolymer is adjusted prior to spray drying to >7, preferably >9, in particular >10. Such a pH of the aqueous solution of the PCE type copolymer used for spray drying results in a finer particle size of the powder copolymer P of the invention and in a powder that is less prone to caking.
[0044] A pH of <7 of an aqueous solution of PCE type copolymer leads to high stickiness and caking during spray drying. According to an embodiment, the pH of the aqueous solution of PCE type copolymer is adjusted according to the number n of repeating units -[AO]-. The higher the number n, the higher the pH needs to be to prevent stickiness and caking during spray drying. According to a particularly preferred embodiment, the number n is between 50 and 115 and the pH is adjusted to at least 10.
[0045] According to an embodiment, the pH is adjusted by the addition of an oxide or hydroxide of an alkali metal, an alkaline earth metal or a mixture thereof. Preferably, the pH of the aqueous solution of the PCE type copolymer is adjusted by the addition of NaOH, KOH, MgO, Mg(OH)2, CaO or Ca(OH)2, with Ca(OH)2 being most preferred.
[0046] Spray drying is a known method of producing dry powders from liquids by combining the rapid drying of a solution with spraying. Drying can be performed with hot gas, preferably hot air or hot nitrogen. The hot gas can be blown in the same direction as the liquid being sprayed. Similarly, the hot gas can be blown in the opposite direction to the liquid being sprayed. The liquid is dispersed with a spray nozzle or atomizer, the inlet of which is preferably at the top of the spray tower. The dried powder can be separated from the hot gas by a cyclone.
[0047] Preferably, the aqueous solution of the PCE type copolymer is preheated before entering the spray dryer. If no gas is used for drying, the PCE type copolymer solution can be introduced into the spray dryer at a pressure of 0.2-40 MPa. If a gas is used for drying, the PCE type copolymer solution can be introduced into the spray dryer at ambient pressure. Preferably, drying is carried out with hot air or hot nitrogen, preferably blown in the same direction as the liquid being sprayed. Spray drying can be carried out at an inlet temperature of 90-300°C, preferably 100-200°C, more preferably 110-150°C, in particular 110-120°C. Lower inlet temperatures have the advantage of lower energy consumption as well as less decomposition of the PCE type copolymer. The outlet temperature can be 55-200°C, preferably 60-150°C, more preferably 65-100°C.
[0048] The aqueous solution of the PCE type copolymer can be introduced into the spray dryer by any means known to those skilled in the art, such as a nozzle, an atomizer or a centrifuge. Any spray dryer known to those skilled in the art is suitable for the production of the powder copolymer P of the invention. The size of the spray dryer can be selected according to the intended throughput.
[0049] According to a preferred embodiment, the powder copolymer P contains other additives. Preferred additives are anti-caking agents and antioxidants which stabilize the powder against thermo-oxidative degradation and auto-ignition.
[0050] Suitable anti-caking agents can be any known to those skilled in the art. Examples of anti-caking agents include powdered cellulose, magnesium stearate, calcium carbonate, dolomite, clay, kaolin, vermiculite, bentonite, talc, slag, fly ash, silicic acid or aluminosilicates, and silicon dioxide, such as fumed silica, precipitated silica, silica gel, or silica sol.
[0051] Suitable antioxidants can be any known to those skilled in the art. Examples of antioxidants are disclosed, for example, in WO 00 / 17263 and include alkylated monophenols, alkylated hydroquinones, alkylidene-bisphenols, benzyl hydroxylates, phenol-thiodiphenyl ethers, acylaminophenols, phenolic esters, and phenolic amides.
[0052] According to an embodiment, any such other additives are added before the spray drying process, as such additives will result in higher performance. The additives can be added to the aqueous solution of the PCE-type copolymer prior to spray drying. Similarly, one or more additives can be added during the spray drying process, for example, via a separate feed nozzle.
[0053] According to an embodiment, the content of any such other additives in the powder copolymer P is less than 5% by weight, preferably less than 2% by weight, more preferably less than 1.5% by weight and in particular less than 1% by weight, each based on the total weight of the aqueous solution.
[0054] The resulting powder product may be sieved to remove any small agglomerates that may have formed.
[0055] The spray drying process can be carried out continuously or discontinuously.
[0056] In a preferred embodiment of the invention, the solid copolymer P is a powder. This powder can be converted into other solid forms, for example by pressing. The copolymer P of the invention can therefore also be in the form of granulates, moulded blocks, tablets etc.
[0057] The powdery copolymers P of the invention have an alkaline reaction with water. They are completely redispersible in water. Such a redispersion in water, with a concentration of the powdery copolymers P of the invention of 40% by weight, has a pH of at least 8, preferably at least 10, in particular at least 11.
[0058] In a further aspect, the present invention relates to a mineral binder or a mineral binder composition, in particular a dry mortar, containing the powder copolymer P of the present invention. The mineral binder is as defined above. The mineral binder composition can be, for example, in the form of a dry composition or in the form of a fluid or hardened binder composition mixed with mixing water. The mineral binder composition can also be in the form of a fully hardened mineral binder composition (for example a moulded body).
[0059] Preferably, the mineral binder or mineral binder composition contains the powdered copolymer P according to the invention in an amount of 0.01 to 10% by weight, preferably 0.05 to 5% by weight, more preferably 0.1 to 2% by weight, in particular 0.15 to 0.8% by weight, based on the total weight of the mineral binder. Due to the improved performance of the powdered copolymer P according to the invention, it is also possible to lower the dosage of said powdered copolymer P in the mineral binder composition.
[0060] The mineral binder composition of the present invention, in particular the dry mortar, may additionally contain aggregate, preferably sand. Sand is a natural granular material composed of fine rock or mineral particles. It is available in various forms and sizes. Examples of suitable sands are quartz sand, limestone sand, river sand or crushed aggregate. Suitable sands are described, for example, in the standards ASTM C778 or EN196-1.
[0061] Preferably, at least a portion of the sand is quartz sand or limestone sand, or a mixture thereof, with quartz sand being particularly preferred because it is chemically inert, strong, available in a variety of sizes, and allows for advantageous control of the fluidity of the composition.
[0062] Typically, the sand is supplied with different proportions of particles that pass through a sieve with effective openings. Preferably, at least 95% by weight of the sand is smaller than 5 mm, more preferably smaller than 4 mm, and even more preferably smaller than 3.5 mm. Larger particles may result in inadequate mixing.
[0063] Preferably, at least a portion of the sand has a particle size of at least 100 μm, more preferably at least 200 μm. Such granulometry provides an optimized particle size distribution for homogeneous mixing, good rheology of the fresh mortar, and high strength of the hardened mortar.
[0064] Preferred sand has a particle size of 0.04 to 5 mm, more preferably 0.05 to 4 mm, and even more preferably 0.05 to 3.6 mm.
[0065] A preferred mineral binder composition according to the invention, in particular a dry mortar, therefore comprises 10-80% by weight, preferably 25-70% by weight, in particular 40-65% by weight, of sand, based on the total dry weight of said mineral binder composition.
[0066] It may be advantageous for the mineral binder composition of the invention, in particular the dry mortar, to additionally contain other additives relating to mineral binder compositions, in particular cementitious binder compositions, which may be, for example, plasticizers, superplasticizers, rheological modifiers, set retarders, air entrainers, deaeration agents, corrosion inhibitors, fibres, synthetic organic polymers, expanding agents, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducing agents and / or antimicrobial agents.
[0067] According to an embodiment, a synthetic organic polymer different from the above PCE type copolymer is contained in the mineral binder composition of the invention. The synthetic organic polymer can be produced by radical polymerization of a monomer selected from the group consisting of ethylene, propylene, butylene, isoprene, butadiene, styrene, acrylonitrile, acrylic acid, methacrylic acid, esters of acrylic acid, esters of methacrylic acid, vinyl esters, vinyl chloride. The synthetic organic polymer is preferably a copolymer synthesized from two or more, preferably two, different monomers. The sequence of the copolymer can be alternating, block or random. Preferred synthetic organic polymers are copolymers of vinyl acetate and ethylene, vinyl acetate, ethylene and methyl methacrylate, vinyl acetate, ethylene and vinyl esters, vinyl acetate, ethylene and acrylic esters, vinyl chloride, ethylene and vinyl laurate, vinyl acetate and vinyl versatate, acrylic esters and styrene, acrylic esters, styrene and butadiene, acrylic esters and acrylonitrile, styrene and butadiene, acrylic acid and styrene, methacrylic acid and styrene, styrene and acrylic esters, and styrene and methacrylic esters.
[0068] The glass transition temperature (Tg) of the synthetic organic polymers can vary within wide limits. Suitable synthetic organic polymers can have a Tg of, for example, from -50°C to +60°C, preferably from -45°C to +50°C, more preferably from -25°C to +35°C.
[0069] It is possible, and in certain instances may be preferred, to use mixtures of two or more of the aforementioned synthetic organic polymers in the compositions of the invention.
[0070] According to an embodiment, the synthetic organic polymer is used in solid form, for example as a redispersible polymer powder. Such a redispersible powder can be produced, for example, by spray drying of a polymer dispersion, as described, for example, in European Patent Application No. 1042391. A suitable redispersible powder is available, for example, under the trade name Vinnapas, from Wacker Chemie AG. The use of a redispersible powder of a synthetic organic polymer is preferred in the present invention.
[0071] Preferred mineral binder compositions, in particular dry mortars, of the present invention therefore comprise: (a) 10 to 50 weight percent of at least one mineral binder; (b) 0.01 to 10% by weight, preferably 0.05 to 5% by weight, more preferably 0.1 to 2% by weight, in particular 0.15 to 0.8% by weight of powdered copolymer P, (c) 0 to 80% by weight, preferably 10 to 65% by weight, of aggregate; (d) 0 to 10% by weight, preferably 0.1 to 6% by weight, of other additives selected from the group consisting of plasticizers, superplasticizers, rheology modifiers, set retarders, air entrainers, deaeration agents, corrosion inhibitors, fibers, synthetic organic polymers, expanding agents, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducers and / or antimicrobial agents, and (e) Optionally, water Includes.
[0072] The mixing of components (a)-(e) can be in any given order by mixers customarily used in the manufacture of mineral binders, mortars or concrete. The mineral binder composition of the present invention, in particular the dry mortar, can be pre-batched in a factory. Similarly, the mineral binder composition of the present invention, in particular the dry mortar, can be mixed at the job site.
[0073] In the context of the present invention, the mineral binder composition is preferably a dry composition, for example a dry mortar composition, and therefore preferably is substantially free of water.
[0074] It has been found that mineral binders or mineral binder compositions containing the above powdered copolymer P have higher fluidity, lower slump loss and higher compressive strength, especially at early stages, when compared to the same mineral binders or mineral binder compositions with a comparative powdered copolymer.
[0075] The powdered copolymer P described above can therefore be used in a method for increasing the flowability of mineral binders or mineral binder compositions.
[0076] The powdered copolymer P can further be used in a method for maintaining the flowability of a mineral binder composition after mixing with water for a defined period of time, for example more than 20 minutes, preferably more than 30 minutes, more preferably more than 45 minutes.
[0077] The powdered copolymer P described above can also be used in a method for reducing the water demand of a mineral binder or a mineral binder composition.
[0078] Finally, the powdered copolymer P described above can be used in a method for increasing the compressive strength of mineral binders or mineral binder compositions, in particular after 1 day and / or 3 days after mixing with water. [Brief description of the drawings]
[0079] [Figure 1] FIG. 1 shows the particle size distribution of the polymer powders P1 and P2 prepared according to the examples below.
[0080] The following examples are illustrative of the present invention and are not intended to limit the scope of the invention in any way. EXAMPLES
[0081] Preparation of polymer solution SP1 330 g of water, 330 g of methallyl polyethylene glycol (OH-terminated, Mw = 4000 g / mol), 42 g of acrylic acid, a 16% aqueous solution of NaOH (102 g), a 10% aqueous solution of Fe(II)SO4·7H2O (1.5 g), and 2 g of sodium hypophosphite were added to a reaction vessel equipped with a stirrer.
[0082] Next, 10 g of a 30% aqueous hydrogen peroxide solution and 4 g of a 5% aqueous Rongalite solution were added dropwise with stirring at a temperature of 20° C. to 35° C. over a period of 70 minutes.
[0083] 120 minutes after the start of the addition, a clear, viscous polymer solution was obtained.
[0084] Preparation of polymer solution SP2 Polymer SP2 was dissolved in 366 g of methallyl polyethylene glycol (OH-terminated, M w = 2400 g / mol) was used, but was prepared similarly to polymer SP1 above.
[0085] Preparation of polymer solution SP3 Partially neutralized polyacrylic acid (M w A 50 wt% aqueous solution (145 g) of methyl 2,4-dichlorophenyl ether (M = 4000 g / mol) and 7.5 g of 50 wt% sulfuric acid were placed in a glass reactor equipped with a thermometer, stirrer, gas inlet tube, and distillation assembly. The solution was heated to 70°C and 52 g of methoxy-terminated polyethylene glycol (M w = 1000 g / mol) and 300 g of methoxy-terminated polyethylene glycol (M w = 3000 g / mol). The mixture was heated under a constant nitrogen flow and maintained at 165°C. After stirring at this temperature for 6 hours, the mixture was cooled to room temperature. The pH of the resulting mixture was about 3.
[0086] Preparation of polymer solution SP4 Polymer SP4 was prepared by mixing 347.5 g of methoxy-terminated polyethylene glycol (M w= 5000 g / mol) was used and prepared similarly to polymer SP3. The pH of the resulting mixture was about 3.
[0087] Preparation of polymer powder P1 3 g of Ca(OH)2, 68 g of water, and 3 g of fumed silica (Aerosil® 150 from Evonik) were added to 200 g of SP1. The resulting suspension had a pH of about 13. The resulting suspension was dried in a laboratory spray dryer (Mini Spray Dryer B-290 (Buechi AG, Switzerland)). Spray drying was performed by introducing the suspension through a nozzle at the head of the spray dryer. Compressed air flowing in the same direction as the sprayed material was used at a flow rate of 600 L / h and a pressure of 0.5 MPa. The inlet temperature was 120°C. The dosing rate was adjusted to reach an outlet temperature of 65-70°C. The charged powder was separated from the air stream by a cyclone.
[0088] Preparation of polymer powder P2 Polymer powder P2 was prepared similarly to polymer powder P1 above, but with the amount of Ca(OH)2 adjusted to 60 mg. The pH of the resulting suspension was about 9.
[0089] Preparation of polymer powder P3 Polymer powder P3 was prepared similarly to polymer powder P1 above, but without the addition of Ca(OH)2. The pH of the resulting suspension was about 5.
[0090] Preparation of polymer powder P4 Polymer powder P4 was prepared similarly to polymer powder P1 above, but using SP2 instead of SP1.
[0091] Preparation of polymer powder P5 Polymer solution SP3 was placed in an open aluminum dish approximately 100 mm in diameter and 7 mm in height, dried at ambient temperature and pressure, and the resulting solid material was ground with a standard mortar and pestle to form a fine powder.
[0092] Preparation of polymer powder P6 Polymer powder P6 was prepared similarly to polymer powder P5 above, using polymer solution SP4 instead of SP3.
[0093] Table 1 below gives an overview of the powders obtained: Polymer powders P1 and P4 are according to the invention.
[0094] [Table 1]
[0095] From Table 1 above it can be seen that spray drying from polymer solution SP1 is only possible if the pH is above 9. If the pH of the polymer solution is only 5, no powder could be obtained. Furthermore, it can be seen that if the pH of the polymer solution is increased to 13, it is possible to obtain a finer powder P with non-caking properties.
[0096] Performance test of cement-like compositions (Examples M1 to M6) As a measure of the fluidity of the cementitious mixture, slump flow tests were performed according to JC / T985-2005 for Examples M1-M3 and GB / T50448-2008 for Examples M4-M6. Slump flow tests were performed on individual samples at specified time points after mixing with mixing water.
[0097] According to standard GB / T17671-1999, compressive strength was measured using 4x4x16cm square columns after the curing times at 23°C / 50% relative humidity as shown in Tables 2-4 below.
[0098] Linear shrinkage was measured after 28 days of curing at 23° C. / 50% relative humidity according to JC / T985-2005.
[0099] For the preparation of examples M1 to M3, 200 g cement (CEM I 52.5), 340 g calcium aluminate cement, 160 g alpha-hemihydrate, 400 g limestone, 860 g quartz sand (0.1-0.3 mm particles) and 4 g each of powders P1, P4 and P6 were dry mixed in a Hobart mixer for 1 minute at 23° C. to obtain a dry mortar.
[0100] The mixing water was added to the dry mix within 10 seconds to give a water / binder ratio of 0.22. Mixing continued for 170 seconds.
[0101] Table 2 below summarizes the results.
[0102] [Table 2]
[0103] These results show that powders P1 and P4 according to the invention have good liquefaction properties and a particularly low loss of slump flow over time. The powders according to the invention also provide a high compressive strength after 1 day as well as a low shrinkage.
[0104] For the preparation of examples M4 to M6, 750 g of cement (CEM I52.5), 120 g of blast furnace slag, 40 g of silica fume, 340 g of fine quartz sand, 120 g of fine river sand (grain size 0.3-0.6 mm), 560 g of coarse river sand (grain size 0.6-2.3 mm) and 2.8 g of each of powders P1, P4 and P5 were dry mixed in a Hobart mixer for 1 minute at 23° C. to obtain a dry mortar.
[0105] The mixing water was added to the dry mix within 10 seconds to obtain a water / binder ratio of 0.15. Mixing continued for 170 seconds.
[0106] Table 3 below summarizes the results.
[0107] [Table 3]
[0108] These results show that powders P1 and P4 according to the invention have good liquefaction properties and a particularly low loss of slump flow over time. The powders according to the invention also give high compressive strengths after 3 days. The present disclosure also includes the following: [1] A powder copolymer P comprising at least 80% by weight, preferably at least 85% by weight, more preferably at least 90% by weight, based on the total weight of the powder, of PCE type copolymers comprising: (a) a molar portion of the structural unit S1 of formula I [ka] (b) b moles of structural unit S2 of formula II [ka] (c) c moles of structural unit S3 of formula III [ka] (d) d molar parts of structural unit S4 of formula IV [ka] During the ceremony, Each M is independently H + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; Each R u each independently represents a hydrogen atom or a methyl group; Each R v represent, independently of one another, hydrogen or COOM, m=0, 1, 2 or 3; p=0 or 1, Each R 1 and each R 2 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -Cycloalkyl, C 1 ~C 20 -alkylaryl, or -[AO]n -R 4 represents Here, A=C 2 ~C 4 - alkylene, and R 4 , H, C 1 ~C 20 -Alkyl, C 1 ~C 20 -cyclohexyl, or C 1 ~C 20 -alkylaryl, and n = 2 to 350, Each R 3 is, independently of the others, NH 2 , -NR 5 R 6 , -OR 7 NR 8 R 9 represents Here, R 5 and R 6 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -cycloalkyl, C 1 ~C 20 -alkylaryl or C 1 ~C 20 -aryl, or hydroxyalkyl- or acetoxyethyl-(CH 3 -CO-O-CH 2 -CH 2 -), or hydroxyisopropyl-(HO-CH(CH 3 )-CH 2 -), or acetoxyisopropyl group (CH 3 -CO-O-CH(CH 3 )-CH 2 -) and; Or R 5 and R 6 together form a ring of which the nitrogen is a part to form a morpholine or imidazoline ring, R 7 is C 2 ~C 4 -alkylene group, Each R 8 and R 9 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -Cycloalkyl, C 1 ~C 20 -Alkyl aryl, C 1 ~C 20 -aryl or hydroxyalkyl group, and a, b, c and d represent the molar parts of the structural units S1, S2, S3 and S4, Where: a / b / c / d=(0.1~0.9) / (0.1~0.9) / (0~0.8) / (0~0.8), where a+b+c+d=1, and The powder copolymer P is a D90 value of <250 μm, preferably <225 μm, in particular <210 μm; A D10 value of <60 μm, preferably <50 μm, in particular <40 μm, and A D50 value of 70 to 130 μm, preferably 75 to 120 μm, in particular 80 to 100 μm The particle size distribution is It is characterized by: [2] Each R 1 and R 2 are mutually independent, -[AO] n -R 4 where each R 4 are each independently H or CH 3 and n is n=8-250, more preferably n=11-200, even more preferably n=20-150, most preferably n=30-125, in particular n=50-115. [3] 2. Powder copolymer P according to embodiment 1, wherein the ratio a / b is between 0.5 / 1 and 15 / 1, preferably between 1 / 1 and 11 / 1, more preferably between 1.5 / 1 and 9 / 1, most preferably between 3 / 1 and 8 / 1, in particular between 6 / 1 and 7 / 1. [4] 2. Powder copolymer P according to embodiment 1, characterized in that it further comprises <5 wt.-%, preferably <2 wt.-%, more preferably <1 wt.-%, of at least one additive selected from the group of anti-caking agents and antioxidants, each based on the total dry weight of the powder. [5] 2. Powder copolymer P according to embodiment 1, characterized in that it has a pH of at least 8, preferably at least 10, in particular at least 11, when redispersed in water at a concentration of 40% by weight. [6] A method for producing a powder copolymer P, comprising the steps of: (i) preparing an aqueous copolymer solution comprising 30-99 wt%, preferably 40-95 wt%, more preferably 50-90 wt%, of a PCE-type copolymer, each based on the total weight of the aqueous solution, comprising: (a) a molar portion of the structural unit S1 of formula I
change
change
change
change
[10] 7. The method of embodiment 6, wherein the copolymer in step (i) is prepared by a radical polymerization process.
[11] The base added in step (ii) is LiOH, NaOH, KOH, Mg(OH) 2 , Ca(OH) 2 or a mixture thereof.
[12] The base added in step (ii) is Ca(OH) 2 and the pH is 10 to 14.
[13] 7. The method according to aspect 6, characterized in that step (iv) is carried out at a spray drying inlet temperature of not more than 150° C., preferably not more than 120° C.
[14] Use of a powdered copolymer P prepared by the method according to any of the embodiments 6 to 13 in a mineral binder composition, preferably a cementitious binder composition.
[15] 15. The use according to claim 14, wherein the mineral binder composition is a dry mortar.
[16] Use of a powdered copolymer P prepared by the method according to any of embodiments 6 to 13 for reducing the water demand of a mineral binder composition.
[17] Use of a powdered copolymer P prepared by the method according to any of embodiments 6 to 13 for increasing the flowability of a mineral binder composition.
[18] Use of a powdered copolymer P prepared by the method according to any of embodiments 6 to 13 for improving the slump life of a mineral binder composition.
[19] Use of a powdered copolymer P prepared by the method according to any of embodiments 6 to 13 for increasing the compressive strength of a mineral binder composition.
[20] A mineral binder composition, in particular a dry mortar, comprising, each based on the total weight of said mineral binder composition: (a) 10 to 50 weight percent of at least one mineral binder; (b) 0.01 to 10% by weight, preferably 0.05 to 5% by weight, more preferably 0.1 to 2% by weight, in particular 0.15 to 0.8% by weight, of a powdery copolymer P prepared by the method according to any one of aspects 6 to 13, (c) 0 to 80% by weight, preferably 10 to 65% by weight, of aggregate (d) 0-10% by weight, preferably 0.1-6% by weight, of other additives selected from the group of plasticizers, superplasticizers, rheology modifiers, set retarders, air entraining agents, deaeration agents, corrosion inhibitors, fibers, synthetic organic polymers, expanding agents, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducers, and / or antimicrobial agents.
[21] 21. The mineral binder composition according to embodiment 20, additionally comprising water.
[22] 22. A molded body obtained by hardening the mineral binder composition according to embodiment 20 or 21.
Claims
1. Powder copolymer P, comprising at least 80% by weight, based on the total weight of the powder, of PCE type copolymers comprising: (a) a molar part of the structural unit S1 of formula I 【Chemistry 1】 (b) b mole parts of structural units S2 of formula II 【Chemistry 2】 (c) c mole parts of structural units S3 of formula III 【Chemistry 3】 (d) d molar parts of structural units S4 of formula IV 【Chemistry 4】 During the ceremony, Each M is independently H + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; Each R u each independently represents a hydrogen atom or a methyl group; Each R v represent, independently of one another, hydrogen or COOM, m=0, 1, 2 or 3; p=0 or 1; Each R 1 And each R 2 are, independently of each other, C 1 ~C 20 -Alkyl, C 1 ~C 20 -Cycloalkyl, C 1 ~C 20 -alkylaryl, or -[AO] n -R 4 represents Here, A=C 2 ~C 4 -alkylene, R 4 is H, C 1 ~C 20 -Alkyl, C 1 ~C 20 -cyclohexyl or C 1 ~C 20 - alkylaryl, and n=2 to 350; Each R 3 is, independently of the others, NH 2 , -NR 5 R 6 , -OR 7 N.R. 8 R 9 represents Here, R 5 and R 6 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -cycloalkyl, C 1 ~C 20 -Alkylaryl or C 1 ~C 20 -aryl, Or hydroxyalkyl- or acetoxyethyl-(CH 3 -CO-O-CH 2 -CH 2 -), or hydroxyisopropyl-(HO-CH(CH 3 )-CH 2 -), or acetoxyisopropyl group (CH 3 -CO-O-CH(CH 3 )-CH 2 -) and Or, R 5 and R 6 together form a ring of which the nitrogen is a part to form a morpholine or imidazoline ring, R 7 is C 2 ~C 4 - an alkylene group, Each R 8 and R 9 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -Cycloalkyl, C 1 ~C 20 - alkylaryl, C 1 ~C 20 represents an aryl or hydroxyalkyl group, and a, b, c and d represent the molar parts of the structural units S1, S2, S3 and S4, Where: a / b / c / d=(0.1 to 0.9) / (0.1 to 0.9) / (0 to 0.8) / (0 to 0.8), However, a+b+c+d=1, and The powder copolymer P is D90 value of <250 μm, D10 value of < 60 μm, and D50 value of 70 to 130 μm and When redispersed in water at a concentration of 40% by weight, it has a pH of at least 8. It is characterized by:
2. Each R 1 and R 2 are each independently -[AO] n -R 4 where each R 4 are each independently H or CH 3 2. Powder copolymer P according to claim 1, wherein n is selected from the group consisting of 1 to 10, and n is from 8 to 250.
3. 2. Powder copolymer P according to claim 1, wherein the ratio a / b is between 0.5 / 1 and 15 / 1.
4. 2. Powder copolymer P according to claim 1, characterized in that it further comprises <5% by weight of at least one additive selected from the group of anticaking agents and antioxidants, each based on the total dry weight of the powder.
5. The method includes the steps of: Method for producing the powder copolymer P: (i) preparing an aqueous copolymer solution comprising 30 to 99 wt. % of a PCE-type copolymer, each based on the total weight of the aqueous solution, comprising: (a) a molar part of the structural unit S1 of formula I 【Chemistry 5】 (b) b mole parts of structural units S2 of formula II 【Chemistry 6】 (c) c mole parts of structural units S3 of formula III 【Chemistry 7】 (d) d molar parts of structural units S4 of formula IV 【Chemistry 8】 During the ceremony, Each M is independently H + , an alkali metal ion, an alkaline earth metal ion, a divalent or trivalent metal ion, an ammonium ion, or an organic ammonium group; Each R u each independently represents a hydrogen atom or a methyl group; Each R v represent, independently of one another, hydrogen or COOM, m=0, 1, 2 or 3; p=0 or 1; Each R 1 And each R 2 are, independently of each other, C 1 ~C 20 -Alkyl, C 1 ~C 20 -Cycloalkyl, C 1 ~C 20 -alkylaryl, or -[AO] n -R 4 represents Here, A=C 2 ~C 4 -alkylene, R 4 is H, C 1 ~C 20 -Alkyl, C 1 ~C 20 -cyclohexyl or C 1 ~C 20 - alkylaryl, and n=2 to 350; Each R 3 is, independently of the others, NH 2 , -NR 5 R 6 , -OR 7 N.R. 8 R 9 represents Here, R 5 and R 6 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -cycloalkyl, C 1 ~C 20 -Alkylaryl or C 1 ~C 20 -aryl, Or hydroxyalkyl- or acetoxyethyl-(CH 3 -CO-O-CH 2 -CH 2 -), or hydroxyisopropyl-(HO-CH(CH 3 )-CH 2 -), or acetoxyisopropyl group (CH 3 -CO-O-CH(CH 3 )-CH 2 -) and Or, R 5 and R 6 together form a ring of which the nitrogen is a part to form a morpholine or imidazoline ring, R 7 is C 2 ~C 4 - an alkylene group, Each R 8 and R 9 are mutually independent, C 1 ~C 20 -Alkyl, C 1 ~C 20 -Cycloalkyl, C 1 ~C 20 - alkylaryl, C 1 ~C 20 represents an aryl or hydroxyalkyl group, and a, b, c and d represent the molar parts of the structural units S1, S2, S3 and S4; Where: a / b / c / d=(0.1 to 0.9) / (0.1 to 0.9) / (0 to 0.8) / (0 to 0.8), where a+b+c+d=1; (ii) adjusting the pH of the aqueous copolymer solution to at least 7 by adding a base; (iii) adding 0.01 to 5 wt. % of at least one additive selected from anti-caking agents and / or antioxidants, each based on the weight of the aqueous copolymer solution; (iv) spray drying the aqueous solution to obtain a powder; and (v) Optionally, screening.
6. The powder copolymer P is D90 value of <250 μm, D10 value of < 60 μm, and D50 value of 70 to 130 μm The particle size distribution is The method according to claim 5, characterized in that
7. Each R in the powder copolymer P 1 and R 2 are each independently -[AO] n -R 4 where each R 4 are each independently H or CH 3 and n is 50 to 115.
8. 6. The process according to claim 5, wherein the ratio a / b in the powder copolymer P is between 0.5 / 1 and 15 / 1.
9. 6. The method of claim 5, wherein the copolymer in step (i) is prepared by a radical polymerization process.
10. The base added in step (ii) is LiOH, NaOH, KOH, Mg(OH) 2 , Ca(OH) 2 or mixtures thereof.
11. The base added in step (ii) is Ca(OH) 2 and the pH is 10 to 14.
12. 6. The process according to claim 5, characterized in that step (iv) is carried out at a spray drying inlet temperature of 150°C or less.
13. Use of a powdered copolymer P prepared by the method according to any one of claims 5 to 12 in a mineral binder composition.
14. 14. Use according to claim 13, characterised in that the mineral binder composition is a dry mortar.
15. Use of a powdered copolymer P prepared by the method according to any one of claims 5 to 12 for reducing the water demand of a mineral binder composition.
16. Use of a powdered copolymer P prepared by the method according to any one of claims 5 to 12 for increasing the flowability of a mineral binder composition.
17. Use of a powdered copolymer P prepared by the method according to any one of claims 5 to 12 for improving the slump life of a mineral binder composition.
18. Use of a powdered copolymer P prepared by the method according to any one of claims 5 to 12 for increasing the compressive strength of a mineral binder composition.
19. 1. A mineral binder composition comprising the following, each based on a total weight of the mineral binder composition: (a) 10 to 50 weight percent of at least one mineral binder; (b) 0.01 to 10% by weight of a powder copolymer P according to any one of claims 1 to 4, (c) 0 to 80% by weight of aggregate (d) 0-10% by weight of other additives selected from the group of plasticizers, superplasticizers, rheology modifiers, set retarders, air entraining agents, deaeration agents, corrosion inhibitors, fibers, synthetic organic polymers, expanding agents, pigments, strength enhancers, waterproofing additives, alkali-aggregate reaction inhibitors, chromate reducers, and / or antimicrobial agents.
20. 20. The mineral binder composition of claim 19, additionally containing water.
21. A molded body obtainable by hardening the mineral binder composition according to claim 19 or 20.
Citation Information
Patent Citations
Method for preparing powdery polycarboxylic acid hyperdispersant
CN101962273A
Powdery cement dispersant
JP2001294463A
Composite cement dispersant
JP2003277114A
Method for producing powdery cement dispersing agent
JP2005272216A
Method for drying concrete dispersant
JP2014524402A